Combined Molybdenum Gelatine Methacrylate Injectable Nano-Hydrogel Effective Against Diabetic Bone Regeneration - Liao X; Shen M; Li T; Feng L; Lin Z; Shi G; Pei G; Cai X (International Journal of Nanomedicine, 2023)
Xun Liao,1,* Mingkui Shen,2,* Tengbo Li,3 Li Feng,3 Zhao Lin,1 Guang Shi,1 Guoxian Pei,3 Xiyu Cai1 1Department of Orthopedics, The Fifth Affiliated Hospital, Sun Yat-sen University, Zhuhai, Guangdong Province, 519000, People’s Republic of China; 2Henan Provincial Third People’s Hospital, Zhengzhou, Henan Province, 450000, People’s Republic of China; 3School of Medicine, Southern University of Science and Technology, Shenzhen, Guangdong Province, 519000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiyu Cai; Guoxian Pei, Email caixirain@163.com; nfperry@163.comIntroduction: Bone defects in diabetes mellitus (DM) remain a major challenge for clinical treatment. Fluctuating glucose levels in DM patients lead to excessive production of reactive oxygen species (ROS), which disrupt bone repair homeostasis. Bone filler materials have been widely used in the clinical treatment of DM-related bone defects, but overall they lack efficacy in improving the bone microenvironment and inducing osteogenesis. We utilized a gelatine methacrylate (GelMA) hydrogel with excellent biological properties in combination with molybdenum (Mo)-based polyoxometalate nanoclusters (POM) to scavenge ROS and promote osteoblast proliferation and osteogenic differentiation through the slow-release effect of POM, providing a feasible strategy for the application of biologically useful bone fillers in bone regeneration.Methods: We synthesized an injectable hydrogel by gelatine methacrylate (GelMA) and POM. The antioxidant capacity and biological properties of the synthesized GelMA/POM hydrogel were tested.Results: In vitro, studies showed that hydrogels can inhibit excessive reactive oxygen species (ROS) and reduce oxidative stress in cells through the beneficial effects of pH-sensitive POM. Osteogenic differentiation assays showed that GelMA/POM had good osteogenic properties with upregulated expression of osteogenic genes (BMP2, RUNX2, Osterix, ALP). Furthermore, RNA-sequencing revealed that activation of the PI3K/Akt signalling pathway in MC3T3-E1 cells with GelMA/POM may be a potential mechanism to promote osteogenesis. In an in vivo study, radiological and histological analyses showed enhanced bone regeneration in diabetic mice, after the application of GelMA/POM.Conclusion: In summary, GelMA/POM hydrogels can enhance bone regeneration by directly scavenging ROS and activating the PI3K/Akt signalling pathway.Keywords: diabetic bone regeneration, nanomaterials, antioxidation